Toward informatics-enabled preparedness for natural hazards to minimize health impacts of climate change. (12th September 2022) - Phuong, Jimmy; Riches, Naomi O; Calzoni, Luca; Datta, Gora; Duran, Deborah; Lin, Asiyah Yu; Singh, Ramesh P; Solomonides, Anthony E; Whysel, Noreen Y; Kavuluru, Ramakanth
Abstract: Natural hazards (NHs) associated with climate change have been increasing in frequency and intensity. These acute events impact humans both directly and through their effects on social and environmental determinants of health. Rather than relying on a fully reactive incident response disposition, it is crucial to ramp up preparedness initiatives for worsening case scenarios. In this perspective, we review the landscape of NH effects for human health and explore the potential of health informatics to address associated challenges, specifically from a preparedness angle. We outline important components in a health informatics agenda for hazard preparedness involving hazard-disease associations, social determinants of health, and hazard forecasting models, and call for novel methods to integrate them toward projecting healthcare needs in the wake of a hazard. We describe potential gaps and barriers in implementing these components and propose some high-level ideas to address them.